Microstructure and Strength Development of Sodium Carbonate-Activated Blast Furnace Slags - Akturk, Busra; Nayak, Sumeru; Das, Sumanta; Kizilkanat, Ahmet B. (ASCE-AMER SOC CIVIL ENGINEERS, 2019)
This paper presents the study of alkali-activated slags where sodium carbonate acts as a primary activator. The slow activation mechanism of sodium carbonate is accelerated by sodium hydroxide and with traces of calcium hydroxide. Strength development and the progress of hydration of the mixes were studied with the phase transformation and development of microstructural features through quantitative techniques such as thermogravimetric analysis and phase-identification techniques such as Fourier transform infrared spectroscopy and X-ray diffraction. Sodium carbonate replacement with sodium hydroxide and the presence of calcium hydroxide in the binder as a replacement for the slag enhances the rate of dissolution of slag, leading to faster strength development. Calcium hydroxide significantly increases the compressive strength, even at an early age. On the other hand, sodium hydroxide substitution is effective at later ages of the reaction when used at high dosages (e.g., 40%). Formation of strength-giving phases such as hydrotalcite and calcium aluminum silicate hydrate are confirmed with microstructure analysis and explain the strength development.
Keywords: Alkali-activated materials; Compressive strength development; Microstructure; Slag; Sodium carbonate; HYDRATION PROPERTIES; THERMAL-PROPERTIES; REACTION-KINETICS; CEMENT; HYDROTALCITE; REACTIVITY; EVOLUTION; PRODUCTS; WASTE; GLASS; Construction & Building Technology; Engineering; Materials Science